Juridical Review by Public Prosecutors in the Criminal Justice System - Dinda, Dinda; Sakti, La Ode Awal; Irabiah, Irabiah (Sangia Nibandera Law Research, 2024)
Constitutional Court Decision Number 20/PUU-XII/2023 states that article 30C letter h and explanation letter h of Law Number 11 of 2021 concerning the Prosecutor's Office of the Republic of Indonesia are contrary to the Constitution of the Republic of Indonesia Year 1945 and have no binding legal force. So this is considered contrary to the purpose of law and legal principles, namely the principle of equality before the law and the principle of equality of arms principle. Therefore, this encourages the author to analyze the concept of judicial review carried out by the Public Prosecutor who actually represents the victim and even the state. The writing of this thesis uses normative juridical research methods with methods of approaching laws and regulations,cases, historical and conceptual. This legal research found that the Criminal Procedure Code for victim protection has not been optimal compared to perpetrators of crimes, where the Criminal Procedure Code only identifies or tends to lead to perpetrators only. Then, with the decision of the Constitutional Court No. 20/PUU-XII/2023, it has the effect of closing the prosecutors authority to be able to apply review as a return of position to the convict.